Non-interventional LUME-BioNIS study of nintedanib plus docetaxel after chemotherapy in adenocarcinoma non-small cell lung cancer: A subgroup analysis in patients with prior immunotherapy. (October 2020) - Reck, Martin; Syrigos, Kostas; Miliauskas, Skaidrius; Zöchbauer-Müller, Sabine; Fischer, Jürgen R.; Buchner, Hannes; Kitzing, Thomas; Kaiser, Rolf; Radonjic, Dejan; Kerr, Keith
Highlights: Subgroup analysis of a non-interventional study in adenocarcinoma NSCLC. Outcomes with nintedanib plus docetaxel after chemo- and immunotherapy (n = 67). Nintedanib plus docetaxel given in third- or later-lines in 57 patients (85.1%). Clinical effectiveness demonstrated: DCR was 78.2% and median OS was 8.8 months. Provides real-world data to inform management in the changing treatment landscape. Abstract: Objectives: To evaluate the effectiveness and safety of nintedanib plus docetaxel in patients with advanced adenocarcinoma non-small cell lung cancer (NSCLC) previously treated with both chemo- and immunotherapy. Materials and methods: LUME-BioNIS is a European, prospective, multicenter, non-interventional study of patients with advanced adenocarcinoma NSCLC, who initiated nintedanib plus docetaxel after first-line chemotherapy in routine practice according to the approved nintedanib EU label. The primary objective is to explore whether molecular biomarkers can predict overall survival (OS). Information on clinical or radiologic progression and death, and adverse drug reactions (ADRs)/fatal adverse events (AEs) was collected during follow-up. Here, we report a subgroup analysis evaluating outcomes in immunotherapy-pretreated patients. Results: Of 260 enrolled patients, 67 (25.8%) had prior immunotherapy and were included in this subgroup analysis. Prior immunotherapy was administered in first-line in 20 patients (29.9%; combined with chemotherapy in 4 patients [6.0%]) and later-lines in 47 patients (70.1%), and most commonly comprised nivolumab (39 patients; 58.2%), atezolizumab (14 patients; 20.9%) and pembrolizumab (11 patients; 16.4%). Nintedanib plus docetaxel was given in second-line in 10 patients (14.9%) and in later-lines in 57 patients (85.1%). Median OS was 8.8 months (95% confidence interval [CI]: 7.0–11.5) and median progression-free survival (PFS) was 4.6 months (95% CI: 3.5–5.7). Among 55 patients with available data, rates of objective response and disease control were 18.2% and 78.2%, respectively. In 65 patients evaluable for safety, the most common on-treatment ADRs/AEs were malignant neoplasm progression (19 patients; 29.2%), diarrhea (21 patients; 32.3%) and nausea (10 patients; 15.4%). Conclusions: Used according to the approved nintedanib label in routine practice, nintedanib plus docetaxel demonstrated clinical effectiveness, with no unexpected safety findings, in patients with prior chemotherapy and first- or later-line immunotherapy. These data add to the real-world evidence that can inform clinical decisions in the changing therapeutic landscape.